Where there’s a will there’s no way. About Griselda Gambaro’s Lo impenetrable (Anclajes, 2024)
Lo impenetrable (1984) is not the most remembered of Griselda Gambaro’s novels, but it is fundamental when thinking about pace and concerns of certain contemporary Argentinian narrative. It proposes sexual and literary displacements or disorientations related to both sexual gender and literary genres. Through the bodily contact enabled by this displacement, lines of association, agency and exchange are created, destabilizing any possibility of fixed and normative identities.
Keywords: Griselda Gambaro; Argentinian Literature; Literary Theory; Gender Studies; XX-XXI century